2016
DOI: 10.1155/2016/9273078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cytotoxic Activity of Rosemary (Rosmarinus officinalisL.), Turmeric (Curcuma longaL.), and Ginger (Zingiber officinaleR.) Essential Oils in Cervical Cancer Cells (HeLa)

Abstract: The objective of this study was to evaluate the cytotoxic activity of rosemary (REO, Rosmarinus officinalis L.), turmeric (CEO, Curcuma longa L.), and ginger (GEO, Zingiber officinale R.) essential oils in HeLa cells. Cytotoxicity tests were performed in vitro, using tetrazolium (MTT) and neutral red assays for evaluation of antiproliferative activity by different mechanisms, trypan blue assay to assess cell viability and evaluation of cell morphology for Giemsa to observe the cell damage, and Annexin V to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…TPG was demonstrated to be non-mutagenic in the bacterial reverse mutation test (Ames test) and negative for clastogenicity and aneugenicity in the in vitro mammalian cell micronucleus test. Cytotoxicity observed in both tests was not associated with any genotoxic activity; on the contrary, in vitro cytotoxicity of turmeric and other botanical extracts may be attributed to their potential use as anticancer agents (Santos et al, 2016).…”
Section: Pathologymentioning
confidence: 75%
See 1 more Smart Citation
“…TPG was demonstrated to be non-mutagenic in the bacterial reverse mutation test (Ames test) and negative for clastogenicity and aneugenicity in the in vitro mammalian cell micronucleus test. Cytotoxicity observed in both tests was not associated with any genotoxic activity; on the contrary, in vitro cytotoxicity of turmeric and other botanical extracts may be attributed to their potential use as anticancer agents (Santos et al, 2016).…”
Section: Pathologymentioning
confidence: 75%
“…Cytotoxicity observed in both tests was not associated with any genotoxic activity; on the contrary, in vitro cytotoxicity of turmeric and other botanical extracts may be attributed to their potential use as anticancer agents (Santos et al, 2016). Cytotoxicity observed in both tests was not associated with any genotoxic activity; on the contrary, in vitro cytotoxicity of turmeric and other botanical extracts may be attributed to their potential use as anticancer agents (Santos et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…(2017) ; Rivera et al. (2017) ; Wang et al., 2017 , Wang et al., 2017 ; Zhou et al., 2016 ; Santos et al. (2016) ; Liu et al.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-proliferative effects of ginger essential oil against HeLa cervical cancer cells are created by cell membrane protrusions, blebbing and chromatin condensation. Increasing the concentration of ginger essential oil to 1928 μl/ml caused the amorphous cells, blebbing and chromatin condensation, which finally caused cell death by apoptosis, similar to those of camptothecin [44]. In other preclinical study, 10 μl/day ginger essential oil for 14 days on acid soluble sulfhydryl levels and hepatic carcinogen metabolizing enzymes (cytochrome P450, aryl hydrocarbon hydroxylase and glutathione-S-transferase) in Swiss albino mice showed that ginger essential oil significantly increased aryl hydrocarbon hydroxylase and glutathione-S-transferase [45].…”
Section: Anticancer Effects Of Ginger Essential Oilmentioning
confidence: 91%